Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1038/s41598-019-51836-z
|View full text |Cite|
|
Sign up to set email alerts
|

Synthetic calcium carbonate improves the effectiveness of treatments with nanolime to contrast decay in highly porous limestone

Abstract: Three synthetized polymorphs of calcium carbonate have been tested in combination with the suspension of nanolime particles as potential consolidating agents for contrasting stone decay and overcome some of the limitations of nanolime agents when applied to substrates with large porosity. The modifications induced in the pore network of the Maastricht limestone were analyzed with microscopy and in a non-invasive fashion with small angle neutron scattering and synchrotron radiation micro-computed tomography. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 65 publications
0
9
0
Order By: Relevance
“…Figure 2b shows an SEM image of SrCO 3 , which demonstrates a flower‐like microstructure where the elongated needle like structures show a highly textured surface, which is consistent with previous observations on the morphology of this material, [29] whereas EDS analysis confirmed that Sr, C, and O are present (Figure 2e). In the case of CaCO 3 , coalesced cubic crystals with a smooth texture was observed (Figure 2c), which is highly indicative of calcite formation, [30] whereas EDS analysis confirmed the presence of Ca, C, and O (Figure 2f). MnCO 3 was found to crystallize in a spherical shape of different sizes, which exhibited a highly textured surface (Figure 2d), consistent with a previous report, [31] and EDS analysis confirmed the presence of Mn, C, and O.…”
Section: Resultsmentioning
confidence: 98%
“…Figure 2b shows an SEM image of SrCO 3 , which demonstrates a flower‐like microstructure where the elongated needle like structures show a highly textured surface, which is consistent with previous observations on the morphology of this material, [29] whereas EDS analysis confirmed that Sr, C, and O are present (Figure 2e). In the case of CaCO 3 , coalesced cubic crystals with a smooth texture was observed (Figure 2c), which is highly indicative of calcite formation, [30] whereas EDS analysis confirmed the presence of Ca, C, and O (Figure 2f). MnCO 3 was found to crystallize in a spherical shape of different sizes, which exhibited a highly textured surface (Figure 2d), consistent with a previous report, [31] and EDS analysis confirmed the presence of Mn, C, and O.…”
Section: Resultsmentioning
confidence: 98%
“…A definitive assessment of the morphology of CaCO 3 crystals was performed using SEM, infrared spectroscopy, and PXRD analysis. Figure a–c shows representative SEM images of CaCO 3 extracted from [CA–MA–PLs]; a combination of different crystal structures of various shapes including pseudocubical, rod-like, and spherical structures were seen, much in resemblance to CaCO 3 crystals reported in the literature. Figure a shows that cubic calcite crystals of sizes 2.5 × 2.7 μm were observed, while in another area within the same sample, different sizes of aragonite rod-like crystals with an average size of 7.6 × 2.2 μm were seen (Figure b); vaterite was also observed in certain regions with an average size of 11 ± 3 μm (Figure c) (average sizes have been provided in the Supporting Information, Figure S19). XRD analysis (Figure d) showed peaks of calcite crystals at 2θ = 23, 29, 31,39, 44, 46, 48, 56, 60, and 65° corresponding to (012), (104), (110), (113), (202), (024), (211), and (214) planes, respectively (PDF#05–0586) .…”
Section: Resultsmentioning
confidence: 99%
“…This technique, when complemented with the elemental information of micro-X-ray fluorescence (μXRF) mapping, becomes particularly well-suited for the micro-analysis of highly heterogeneous systems, especially when the new phases are present in minor fractions if compared to the substrate’s minerals or are poorly crystalline. These techniques, although well-known and already used in many fields over the years 31 35 , in CH materials are mainly used in the examination of oil paintings 22 39 and wall paintings 40 , 41 , ceramics 42 , 44 , paper 45 , and metals 46 , 47 , but, to the best of our knowledge, have not been employed to study the reaction products of inorganic consolidation solutions on porous carbonate stones in CH.…”
Section: Introductionmentioning
confidence: 99%